2021
DOI: 10.1620/tjem.254.41
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Binge Drinking and Alcohol-Related Consequences and their Relationship among Japanese College Students

Abstract: Binge drinking is a common and risky behavior among college students. In Japan, however, research on the prevalence of binge drinking and alcohol-related consequences, and the relationship between them, is currently scant. The aim of this study is to examine the status of binge drinking and alcohol-related problems, and the relationship between them, among Japanese college students. We conducted a crosssectional survey of college students who participated in a health seminar or lecture including alcoholrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Universities and other educational institutions can be the perfect environment for raising students’ awareness of the problems of using not only alcohol, but also other addictive substances that are associated with alcohol use disorders (tobacco and cannabis). In respect to the continuing threat of the COVID-19 pandemic, it is essential that public health leaders, researchers, health professionals and parents understand the importance of improving health literacy with an emphasis on substance use, as they can have lasting effects on the health and social position of university students [ 9 , 10 , 11 , 12 ]. In addition to providing information on current research, risks, guidance on early identification and other interventions for alcohol consumers, university education should not be left without motivating students to lead a healthy lifestyle without drinking alcohol, but also without smoking tobacco and cannabis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universities and other educational institutions can be the perfect environment for raising students’ awareness of the problems of using not only alcohol, but also other addictive substances that are associated with alcohol use disorders (tobacco and cannabis). In respect to the continuing threat of the COVID-19 pandemic, it is essential that public health leaders, researchers, health professionals and parents understand the importance of improving health literacy with an emphasis on substance use, as they can have lasting effects on the health and social position of university students [ 9 , 10 , 11 , 12 ]. In addition to providing information on current research, risks, guidance on early identification and other interventions for alcohol consumers, university education should not be left without motivating students to lead a healthy lifestyle without drinking alcohol, but also without smoking tobacco and cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nasui et al [ 8 ], both male and female university drinkers engaged in other risky behaviours correlated with drinking. These patterns of behaviour have many consequences, whether it is a threat to health and life [ 9 ], reduced academic performance, missed classes and lower grades, memory blackouts, changes in brain function, lingering cognitive deficits, sexual assaults [ 10 ], but also poor mental health [ 11 ] or social problems [ 12 ]. Regarding determinants, it is well known that the male gender characteristic is a significant factor associated with increased alcohol use [ 13 , 14 ] and is therefore considered a predictor of alcohol use disorders [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been comparatively little research on BD in Japan and previous studies have produced different estimates depending on the specific population being studied and how BD has been defined. A recent study among Japanese college students that used the same definition of BD as in this study showed that the prevalence of BD was high among both men (55.7%) and women drinkers (46.2%) ( Kawaida et al, 2021 ). In contrast, a study that used nationwide data from three cross-sectional surveys undertaken in Japan in 2003, 2008 and 2013 found that the age-adjusted prevalence for the total population ranged between 4.5-6.4% when BD was defined as consuming 60 g or more of alcohol on one drinking occasion, one or more times a week.…”
Section: Discussionmentioning
confidence: 80%
“…Given that the minumum legal drinking age is 20 in Japan this may have affected our results although it has been reported that underage drinking is common and a significant social problem in the country ( Higuchi et al, 2007 ) Finally, we used an adapted question from the US National Institute on Alcohol Abuse and Alcoholism to assess BD. As what constitues a standard drink differs between the US and Japan ( Kawaida et al, 2021 ) it is uncertain how appropriate this measure was to accurately assess BD in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation